Vitamins A and D and zinc affect the leshmanicidal activity of canine spleen leukocytes - Hernandez, Fabiana M. de O. [UNESP]; Santos, Marilene O. [UNESP]; Venturin, Gabriela L. [UNESP]; Bragato, Jaqueline P. [UNESP]; Rebech, Gabriela T. [UNESP]; Melo, Larissa M. [UNESP]; Costa, Sidney F. [UNESP]; de Freitas, Jéssica H. [UNESP]; Siqueira, Carlos Eduardo [UNESP]; Morais, Déborah A.; Júnior, Wellington T. de S.; Júnior, Fernando B.; et al. (My University, 2021)
Canine leishmaniasis (CanL) is a chronic disease caused by Leishmania infantum, and the limitations of the current treatments have encouraged new alternatives, such as the use of immunomodulatory nutrients. The objective of this study was to determine the serum levels of vitamin A (retinol), vitamin D (25(OH)VD3), and zinc (Zn) in dogs with CanL and the effect of in vitro supplementation with the respective active forms ATRA, 1,25(OH)2VD3, and SZn on spleen leukocyte cultures. Serum retinol, 25(OH)VD3, and Zn were determined by HPLC, ELISA, and ICP-MS, respectively. Spleen leukocyte cultures were used for the detection of NO and ROS by flow cytometry; the IFN-γ, TNF-α, and IL-10 levels were determined by ELISA; and the parasite load was determined by microscopy. We detected low serum levels of retinol and Zn and high levels of 25(OH)VD3 in the CanL group. The in vitro supplementation of CanL spleen leukocytes with ATRA, 1,25(OH)2VD3, and SZn, in addition to a soluble leishmania antigen (SLA) treatment, increased the NO and ROS levels, while the treatments with only ATRA and SZn increased the TNF-a levels. Increased IL-10 and IFN-g levels were observed with the addition of SLA to the medium, although the addition of the three nutrients led to a reduction of the IL-10 levels, and the addition of 1,25(OH)2VD3 and SZn led to a reduction of IFN-g. A supplementation with 1,25(OH)2VD3 and SZn reduced the parasite load but only in the absence of SLA. We suggest that the nutrients we tested are involved in the leishmanicidal mechanism, showing a potential for investigation in future studies.
Keywords: All-trans retinoic acid; Leishmania spp; Retinol; Vitamin D3; Zinc